Optimalisasi Inovasi Produk Gurami Beku: Studi Kasus Pemberdayaan Masyarakat di Desa Tegalwangi, Kecamatan Umbulsari - Seta, Dowan Rahma; Santosa, Marita Yayang; Andalusia, Sofi Cordova; Takbirryansyah, Alfian; Parahitha, Caesar Daffa; Sanjaya, Annisa Syifa; Jannah, Nur Akhillah Roikhatul; Prasetya, Ahmad Fada; Febriyanti, Okke Silvi; Alvandio, Christopher; Farianto, Inas Thohirah; Sasabila, Dinda Natalia; Tarigan, Yevia Clara; Valentino, Brilliant Tri; Putri, Zalfa Alayya Eka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Tegalwangi Village, located in Umbulsari Subdistrict, Jember Regency, has significant potential for gourami fish farming, making it the largest gourami farming center in the district. However, the low public interest in raw gourami fish has hindered its marketability. Therefore, product innovation is necessary to facilitate gourami fish consumption. One such innovation is frozen gourami products. This program aims to empower Tegalwangi Village residents as entrepreneurs through four stages: socialization, training, mentoring, and marketing. During the program implementation, 30 individuals participated in training, and 10 entrepreneurs were coached by the PPK Ormawa HMPWK Team. The program has enhanced residents' knowledge of frozen gourami production. The community successfully produced quality frozen gourami and marketed the products to the public. This initiative is expected to address low fish consumption and limited market access while serving as an alternative to improve the local economy.